2022
DOI: 10.3389/fpsyt.2022.992404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of positive and negative affect on self-management among patients with early chronic kidney disease during the COVID-19 pandemic: The mediating and suppressing effect of ego depletion

Abstract: BackgroundSelf-management in patients with early chronic kidney disease (CKD) can effectively delay damage to renal function. However, with the continuous spread of COVID-19, patients cannot receive timely treatment, which can lead to different affects, resulting in ego depletion and serious challenges to self-management. This study aimed to investigate the mediating and suppressing roles of ego depletion on the relationship between positive and negative affect and self-management among patients with early CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Patient satisfaction is particularly vulnerable to social psychological factors because of the inherent information asymmetry, unequal power dynamics, and frequent interactions between doctors and patients, which make it distinct from traditional customer satisfaction metrics ( Croker et al, 2013 ; Xesfingi and Vozikis, 2016 ). Our mediating effects analysis indicated that the direct and indirect effects of the social cognition of the medical environment on patient satisfaction are contradictory, likely due to the suppressive effect of social desirability bias on this relationship ( Cui et al, 2022 ). To address these complexities, it is essential to acknowledge the influence of social desirability bias when evaluating patient satisfaction.…”
Section: Discussionmentioning
confidence: 97%
“…Patient satisfaction is particularly vulnerable to social psychological factors because of the inherent information asymmetry, unequal power dynamics, and frequent interactions between doctors and patients, which make it distinct from traditional customer satisfaction metrics ( Croker et al, 2013 ; Xesfingi and Vozikis, 2016 ). Our mediating effects analysis indicated that the direct and indirect effects of the social cognition of the medical environment on patient satisfaction are contradictory, likely due to the suppressive effect of social desirability bias on this relationship ( Cui et al, 2022 ). To address these complexities, it is essential to acknowledge the influence of social desirability bias when evaluating patient satisfaction.…”
Section: Discussionmentioning
confidence: 97%
“…There are several plausible explanations. First, the results may be influenced by different research periods, contexts, and populations, especially regarding the type and extent of negative effects ( 58 ). Second, the descriptive statistics showed that over 95% of Chinese university students in our final sample had AP-SRTm (i.e., entertainment and lifestyle information), which is much higher than their AP for other types.…”
Section: Discussionmentioning
confidence: 99%
“…When taking into account all variables (including covariates), the results of mediating analysis suggest that all of the fit indexes were within the acceptable range, specifically the chi-square test ðχ 2 Þ = 261:516, degree of freedom ðdf Þ = 130, χ 2 /df = 2:01 < 4, root mean square error of approximation ðRMSEAÞ = 0:058 < 0:08, comparative fit index ðCFIÞ = 0:961 > 0:95, Tucker-Lewis index ðTLIÞ = 0:952 > 0:95, CFI/TLI = 1:01 > 0:9, and standardized root mean square residual ðSRMRÞ = 0:066 < 0:08 [46]. Table 5 shows the 95% CI of each path, and Figure 3 presents the structural equation model.…”
Section: Mediating Analysismentioning
confidence: 99%